Diagnostic pitfall in primary cervical gestational choriocarcinoma: a case report - Shi, Jiayu; Chen, Ping (Frontiers in Oncology, 2025)
Choriocarcinoma belongs to a group of highly aggressive malignant gestational trophoblastic neoplasms. Choriocarcinoma is classified into two types based on the origin: a gestational type that arises following a normal or abnormal pregnancy and a non-gestational type resulting from trophoblastic differentiation of germ cells or somatic carcinomas. Primary cervical choriocarcinoma is rare; in women without a recent pregnancy, it is frequently misdiagnosed as other cervical carcinomas, which typically require surgery. Herein, we present a case of primary cervical choriocarcinoma in a 47-year-old woman who presented with irregular vaginal bleeding for five months, with her last pregnancy six years ago. She was initially misdiagnosed with cervical squamous cell carcinoma. Further evaluations, including serum human chorionic gonadotropin (hCG) and comprehensive pathological evaluation, confirmed the diagnosis of gestational choriocarcinoma. Immunohistochemistry showed positive hCG staining, negative p40 and p63 staining, and a high Ki-67 index (60%). Choriocarcinomas of the cervix are uncommon and share similar morphological characteristics with squamous cell carcinoma. Following systemic chemotherapy, hCG levels markedly declined, and the lesion resolved with good response. This case highlights the diagnostic pitfalls associated with primary cervical gestational choriocarcinoma and the importance of clinical correlation, particularly in patients without a recent pregnancy.